2015
DOI: 10.1016/j.jpsychires.2015.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Collective unconscious: How gut microbes shape human behavior

Abstract: The human gut harbors a dynamic and complex microbial ecosystem, consisting of approximately 1 kg of bacteria in the average adult, approximately the weight of the human brain. The evolutionary formation of a complex gut microbiota in mammals has played an important role in enabling brain development and perhaps sophisticated social interaction. Genes within the human gut microbiota, termed the microbiome, significantly outnumber human genes in the body, and are capable of producing a myriad of neuroactive com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
329
0
25

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 460 publications
(358 citation statements)
references
References 72 publications
4
329
0
25
Order By: Relevance
“…The human adult gut contains over 1kg of bacteria, essentially the same weight as the human brain 1 . It is generally estimated that the gut is inhabited by 10 13 -10 14 microorganisms, which is more than ten times the number of human cells in our bodies and contains over 100 times as many genes as in our genome 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The human adult gut contains over 1kg of bacteria, essentially the same weight as the human brain 1 . It is generally estimated that the gut is inhabited by 10 13 -10 14 microorganisms, which is more than ten times the number of human cells in our bodies and contains over 100 times as many genes as in our genome 2 .…”
Section: Introductionmentioning
confidence: 99%
“…This situation may influence the evolution and dynamics of a variety of inflammatory diseases. Microbiome genes within the human gut microbiota, which significantly outnumber human genes in the body, can produce a plethora of neuroactive proteins/peptides [2].…”
Section: Introductionmentioning
confidence: 99%
“…Mazurek et al suggest that gastrointestinal problems are interrelated with and possibly have common underlying mechanisms with anxiety and sensory over-responsivity in ASD children [96]. Others have recently supported this hypothesis as well [97][98][99] In a mechanistic approach these recent works support the 1994 study by Stefano and colleagues, who suggested inappropriately activated immune cells could and do wander into the brain releasing common chemical messengers and that in so doing stimulates abnormal behavioral outcomes, e.g., autism-like.…”
Section: Environmental Factorsmentioning
confidence: 89%